ANALISIS DISPENSASI NIKAH AKIBAT PERNIKAHAN DINI DALAM PERSPEKTIF PEMENUHAN HAK ISTRI DAN ANAK (STUDI KASUS PENETAPAN NOMOR 22/PDT.P/2023/PA.SKH) - Sintianingrum, S; Syamsuddin, S; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
In carrying out a marriage, it is important to pay attention to children's rights so that they are fulfilled without compromising the purpose of the marriage itself. Children under 18 years of age are considered a group that needs special protection and fulfillment of their rights in accordance with the provisions of this law. The formulation of the problem in this research is how the marriage practices of prospective brides at an early age occur at the Office of Religious Affairs in Grogol District, what are the legal considerations of judges regarding decision No. 22/PDT.P/2023/PA.SKH and How to fulfill the rights of wives and children during the marriage process This research is qualitative research with in-depth field research regarding certain cases using observation, interview and documentation data collection methods. The results of this research are that the practice of marrying prospective brides at an early age at the Grogol Subdistrict Religious Affairs Office is that a marriage is carried out where the person is still a minor. It may be carried out if there is a positive impact, such as avoiding immoral acts or the occurrence of something undesirable. The judge's legal considerations regarding decision no. 22/PDT.P/2023/PA.SKH stipulates that judges consider that